MORFOLOGI Bruguiera cylindrica (L.) Blume YANG TUMBUH DI HUTAN MANGROVE KECAMATAN SIBERUT UTARA KABUPATEN KEPULAUAN MENTAWAI - Rizki, Rizki; Safitri, Elza; Asroen, Asroen (Sainstek : Jurnal Sains dan Teknologi, 2015)
Morphology is the result of expression of a genotype that is influenced by environmental factors. Plant morphological variations may occur due to the different conditions of the region, these conditions may include differences in geographical location, ecological conditions such as variations in temperature, humidity, nutrition and others. Has done research on the morphology of Bruguiera cylindrica (L.) Blume grown in mangrove forest districts North Siberut Mentawai District. This morphological study aims to determine the morphology B. Cylindrica and compare it with the data that has been there before. This study was conducted in May-June 2015 in the mangrove forest District of North Siberut Mentawai District. The research method used in the study was a survey and a collection directly in the field. Samples contained area of mangrove forests are taken at random and then proceed to describe the morphology of the species B. Cylindica structure. Based on the research that has been dilakkan B. cylindrica can diketahuhi there are some differences in morphological characters on the roots of these species such as shape, color roots, tree height, color of trunks and branches, filotaksis leaves, leaf color, leaf length, flower color, fruit color, length and the diameter hipokotil. Then from this study can also be added some new information that has not been previously reported.Key word: morfologi Bruguiera cylindrica (L.) Blume, mangrove, mentawai